Peculiarities of the root-suckering ability of Hippophae rhamnoides L. plants (East Kazakhstan region) - Vdovina, T.; Lagus, Olga; Isakova, E (Fundamental and Experimental Biology, 2025)
The article presents data on the root-suckering ability of Hippophae rhamnoides L. in various ecological and geographical conditions of natural populations, in a selection area and in an introduced population Altai Botanical Garden. According to the age structure, natural populations of this species are classified as fast-growing and stable. The lifespan of plants ranges from 16 years in the Karatal population to 32 years in the Tersayryk population. In culture, some forms and seedlings are 38 years old. By the number of root shoots H. rhamnoides L. in natural habitats and in the introduced population (clumps) the proportion of plants of the first and second age groups is high. In natural populations there are from 540 pcs/ha to 5173 pcs/ha of plants of the first age group, in the clumps of the introduced population from 1353 pcs/ha to 2076 pcs/ha, which in percentage terms is 30-79%, 50-69%, respectively. In the second age group in natural habitats there are plants from 380 pcs/ha to 556 pcs/ha, in clumps from 457 pcs/ha to 844 pcs/ha. Undoubtedly, the influence of genes and environmental factors on the high root-suckering ability of plants is affected. The most optimal number of root suckers from 16 to 30 pcs per 12 m2 in a breeding garden allows obtaining high-quality planting material. H. rhamnoides L. of the East Kazakhstan ecotype has a high root-suckering ability, which allows it to be recommended as a melioration plant. It is characterized by high winter hardiness and longevity.